Ongoing Dispersal of the 7 August 2019 Pumice Raft From the Tonga Arc in the Southwestern Pacific Ocean. Issue 5 (2nd March 2020) - Jutzeler, Martin; Marsh, Robert; van Sebille, Erik; Mittal, Tushar; Carey, Rebecca J.; Fauria, Kristen E.; Manga, Michael; McPhie, Jocelyn
Abstract: On the 7 August 2019, a 195 km 2 raft of andesitic pumice was produced at 200 m below sea level at an unnamed submarine volcano in the Tonga Islands (Southwest Pacific Ocean). Drifting chiefly westward, the raft reached the Fiji Islands on the 19 September. Yachts that crossed the raft as early as 2 days post‐eruption provided an outstanding data set of raft characteristics and pristine samples. Further, exceptional tracking of raft dispersal by satellite images allows us to contrast virtual particle tracking methods with ocean model currents to explore the relative influence of surface currents, wind, and wave action on pumice flotsam dispersal over up to 2 years. Attenuation of ocean waves by large and compact pumice rafts appears to reduce the effect of Stokes drift. The coupling of real‐time satellite observations with oceanographic Lagrangian simulations allows near‐real time forecasting for global maritime hazard mitigation. Plain Language Summary: Although 70% of volcanism occurs underwater, submarine eruptions are seldom witnessed owing to their remoteness and absence of technologies enabling their detection. On the 7 August 2019, a submarine volcanic eruption 200 m below sea level in the Tonga Islands formed a 195 km 2 pumice raft. The raft was first encountered and sampled by yacht crews, and is visible on satellite images. Pumice rafts are dispersed by ocean currents, wind, and waves, and can cross entire oceans or get stranded on coasts. After 7 weeks of dispersal, the pumice raft reached the Fiji Islands, and a fraction continued its westward route toward Vanuatu and eastern Australia. Excellent imaging of the raft by satellites permitted reconstruction of daily raft dispersal for the first 8 weeks. Here we show that drift calculations, including components of ocean current, wind, and wave action, can usefully forecast raft dispersal. We tested and tuned these drift calculations by comparing the simulated drift with daily satellite images of the raft. Further, a combination of satellite images and drift calculations based on oceanographic models were used for maritime hazard mitigation in near‐real time. Key Points: A >30 million m 3 pumice raft formed at an unnamed volcano in Tonga midday on the 7 August 2019 and was dispersed by ocean currents and wind Forecasts of pumice raft dispersal, based on particle drift with model currents, winds, and waves, are evaluated with daily satellite images Stokes drift does not improve short‐term predictions on large and compact pumice rafts because these rafts attenuate ocean waves